Acute kidney injury in a pediatric intensive care unit - Martins,João Rio (2019)
Background and aims: Acute kidney injury (AKI) is a common condition in Pediatric Intensive Care setup and has been associated with increased mortality and morbidity. The aim of this study was to determine incidence, risk factors, and outcome of AKI in a Pediatric Intensive Care Unit (PICU). Materials and methods: An exploratory study was conducted using prospective data collected from July to December 2017. Clinical and biochemical data from all patients admitted to PICU was recorded. Kidney Disease: Improving Global Outcomes (KDIGO) criteria were used for diagnosis. Patients with hospital stay shorter than 48 hours and with previously documented kidney disease were excluded. Results: During the study period, 32 of 112 children developed AKI (28.6%). Median time of diagnosis was on the second day of admission. Overall, 59.4% of children fulfilled creatinine criteria, 68.8% urinary output criteria, and 28.1%, both. KDIGO stages 1, 2 and 3 accounted for 50.0%, 28.1%, and 21.9% of cases, respectively. Total renal function recovery occurred in 56.3% of cases, partial recovery in 28.1%, and 15.6% of cases did not recover. Invasive ventilation (p=0.028), need for vasoactive drugs (p=0.043), and shock (p=0.043) were independent risk factors for AKI. Mortality was higher in AKI (15.6%) than in non-AKI (1.3%) patients (p=0.007). Discussion: AKI is common in PICU setting, especially in the first days of admission. Both serum creatinine and urinary output criteria should be considered for diagnosis. Use of mechanical ventilation and/or vasoactive drugs and shock are common risk factors and should elicit careful monitoring and prompt treatment.